Edukasi Personal Hygiene Saat Menstruasi pada Siswi SMP Negeri 25 Kota Jambi - Hesty Hesty; Nurfitriani Nurfitriani (Jurnal Abdimas Kesehatan (JAK), 2023)
Self-care during menstruation is important to maintain cleanliness and prevent infection. The Ministry of Health strives for cleanliness during menstruation by notifying three school health efforts (Trias UKS). This effort is made so that adolescents who have just menarche or are experiencing menstruation for the first time can know and understand the importance of maintaining hygiene during menstruation, and the impact that will occur if not maintaining cleanliness during menstruation will be vulnerable to urinary tract disorders (UTI), disturbances in the reproductive tract. and irritation of the skin, especially the skin of the female genitalia. One effort that can be done to maintain reproductive health in women is to maintain feminine hygiene during menstruation. This education is provided in order to increase knowledge about personal hygiene during menstruation for female students, so that it does not cause other health impacts on the reproductive organs. Methods of dedication through lectures, discussions and questions and answers and demonstrations. The target of education is 20 students at SMP Negeri 25 Jambi City. Based on the results of the activity, it was found that there was an increase in knowledge of young women about personal hygiene during menstruation and being able to practice it during menstruation. It is recommended that the UKS at SMP Negeri 25 Jambi City improve educational activities in collaboration with the health team in the nearest area.